Social museology, Sociomuseology, and a dash of technology (Cadernos de Sociomuseologia, 2025)
This article maps the similarities and distinctions between the terms “Social Museology” and “Sociomuseology” in the literature, evaluating the use of AI tools as a methodological aid. The exploratory and theoretical research analyzed 50 articles from the journal Cadernos de Sociomuseologia (1993-2022). The results show that both terms emerged from New Museology in the 1990s, sharing commitments to social action, community participation, interdisciplinarity, and criticism of traditional museology. Despite the similarities, which sometimes lead to synonymy (with regional nuances, such as “Social Museology” in Brazil and “Sociomuseology” in Portugal), important distinctions can be observed. Sociomuseology is often presented as a science in formation or a school of thought. Social Museology, on the other hand, tends to focus on direct practices of intervention and social transformation. However, it is proposed that the latter be seen as a perspectivist know-how based on the commonality of struggle and the former as an approach to update and broaden the principles of New Museology from which both originated.KEY WORDS: Social Museology, Sociomuseology, New Museology, Comparative Analysis, Artificial Intelligence.